1995
DOI: 10.1111/j.1464-5491.1995.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Practice Based Diabetic Eye Screening Programme

Abstract: In many cases, blindness due to diabetic retinopathy can be prevented provided treatment with laser photocoagulation is used at the correct time. A screening programme is required to identify cases of sight threatening retinopathy. An optical practice based diabetic eye screening programme has been established in Dorset. The optometrist undertaking the examination is paid a fee. The findings are recorded on a coded form and sent to the hospital diabetologist who recalls positive cases. Seventy-six optical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…These were subsequently found to be indispensable and were made permanent in the Health Services and Public Health Act 1968 and renamed the General Ophthalmic Services (GOS). Over the years, the responsibilities of the GOS were increased and they now include contact lens work, glaucoma screening, 22 23 selective diabetic retinopathy screening [24][25][26] and experimental trials of the follow up of glaucoma patients, 27 cataract surgery, 28 and the referral of cataract patients directly to the hospital. 29 Extending the optometrists' role to treatment of disease and becoming the principal providers of primary ophthalmic care in the community has been proposed 20 and the prescription of therapeutic drugs by optometrists is being considered, 30 but these suggestions have not been approved by the Royal College of Ophthalmologists.…”
Section: Characteristics Of the Primary Care Led Nhsmentioning
confidence: 99%
“…These were subsequently found to be indispensable and were made permanent in the Health Services and Public Health Act 1968 and renamed the General Ophthalmic Services (GOS). Over the years, the responsibilities of the GOS were increased and they now include contact lens work, glaucoma screening, 22 23 selective diabetic retinopathy screening [24][25][26] and experimental trials of the follow up of glaucoma patients, 27 cataract surgery, 28 and the referral of cataract patients directly to the hospital. 29 Extending the optometrists' role to treatment of disease and becoming the principal providers of primary ophthalmic care in the community has been proposed 20 and the prescription of therapeutic drugs by optometrists is being considered, 30 but these suggestions have not been approved by the Royal College of Ophthalmologists.…”
Section: Characteristics Of the Primary Care Led Nhsmentioning
confidence: 99%
“…The industrialised countries of western Europe, together with countries such as the Czech Republic, Estonia, Hungary, Poland, and Slovakia, have been considering diabetic retinopathy among the leading causes of avoidable blindness in their population during the last decades. [97][98][99][100][101][102][103][104][105][106][107] In the above mentioned parts of Europe, early diagnosis and systematic follow up of diabetic patients have been promoted. In rural areas of former socialist countries of the Balkan Peninsula, and in some former USSR member countries, healthcare services providing early detection and/or retinal laser treatment are not often available.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…[14][15][16] The proportion of patients undergoing process of care in Dorset is similar to these studies, and was consistent with previously reported percentages of patients undergoing the process of care by GPs in Poole. 12 The numbers of patients undergoing retinal screening seems low compared with previously published data on the optometrist-based eye screening programme in Dorset, 18 but discussion with local GPs suggests that the data collection process may cause difficulties, and that we are probably underestimating the numbers of patients having their eyes screened. However, this system of data collection has not changed between 1996 and 2001, so the fall in numbers of patients having their eyes screened reported in our study may not be due to this problem.…”
Section: Discussionmentioning
confidence: 97%